Programa de habilidades sociais em situação natural de trabalho de pessoas com deficiência : análise dos efeitos - Campos, Juliane Aparecida de Paula Perez (2006)
Some social skills are crucial to contribute to friendship formation, social support and work satisfaction; moreover, the social skilled behaviors have been identified as a pre requisite for workers with disabilities to have a good performance and to maintain their jobs in the competitive world. The main objective of the present research was to elaborate, to apply and to analyze the effects of a Social Skills Program for Work (PHST) with workers with physical and mental deficiency in natural work situations. The selection of the participants took place after a initial study about the instrument construction on social abilities. The selected workers to participate in this study were one female and two males, with ages ranging from 21 to 36 years old. In order to characterize the selected participants it was used a questionnaire about professional performance and a structured interview. In order to achieve the study objective, a multiple probe design was employed baseline, intervention and probes), being the PHST the independent variable and the quality of performance on social skills was the dependent variable evaluated by the instrument: PRQDHS: Protocol to register the level of performance quality on social skills throughout the experimental design. The results indicated a gradual increase in the performance of social skills, such as: to question if there were things to do; to offer and ask for help; to talk about personal needs. Those aspects were worked with participants and their job colleagues. Since this area is nationally still under investigation, other studies are suggested as well as a training of the job colleagues in the promotion of social repertoires of workers with deficiency